The moving umbilicus: Beevor’s Sign - Atiquzzaman, Md; Hasan, Md Hashibul; Sohan, Md Ashikuzzaman; Akhtar, Farzana (Bangladesh Critical Care Journal, 2022)
Abstract not available Bangladesh Crit Care J September 2022; 10(2): 166-167